Exploring opportunities and challenges for achieving the integration of indigenous knowledge systems into environmental education processes: a case study of the Sebakwe Environmental Education programme (SEEP) in Zimbabwe - Zazu, Cryton (Rhodes University, Faculty of Education, Department of Education, 2007)
The role and value of indigenous knowledge systems in enhancing and contextualizing education has long been recognized (UNESCO, 1978). Against this background a lot of research focusing on the documentation and study of the world's indigenous knowledge systems, including those of Southern African countries was done. However, within the Southern African context much of this research did not translate into practical curriculum processes leaving educational processes de-contextualized (O'Donoghue, 2002; Mokuku, 2004; Shava, 2005). The linkages between the school, the home and the wider community remained weak (Taylor & Mulhall, 2001). The net effect of the limited integration of indigenous knowledge systems into mainstream environmental education processes has been that indigenous learners (such as those within the Sebakwe rural community) continued to get exposed to two different world views, the western scientific world view and the everyday life world views. The integration of indigenous knowledge systems into mainstream education such as the Sebakwe Environmental Education programme (SEEP) is one way of contextualizing education and improving its relevance to learners' socio-cultural backgrounds. This research was conceptualized against such a context and seeks to explore the opportunities and challenges for the integration of indigenous knowledge systems into the Sebakwe Environmental Education programme. The ultimate purpose of this research is to contextualize SEEP both in its epistemology, and pedagogy. The research was designed and conducted within a qualitative interpretive case study methodology. The methodology involved a three-phased data collection method namely document analysis, focus group interviews and an inquiry-based workshop. The data was then analyzed and interpreted in relation to a set of theoretical perspectives. This research concluded that there is a possibility of integrating indigenous knowledge systems into the Sebakwe Environmental Education programme. Based on the findings the research came up with a list of recommendations to guide the process of working with indigenous knowledge within the Sebakwe Environmental Education programme.
Keywords: Sebekwane Environmental Education programme; Ethnoscience -- Study and teaching -- Zimbabwe; Environmental education -- Zimbabwe; Mainstreaming in education -- Zimbabwe